Commentary on "An intermediate state between the kagome-ice and the fully polarized state in Dy2Ti2O7" - Mauro Perfetti (Papers in physics, 2015)
A Commentary on the paper by S A Grigera et al. [Pap. Phys. 7, 070009 (2015)]. Received: 25 June 2015, Accepted: 25 June 2015; Edited by: A. Vindigni; DOI: http://dx.doi.org/10.4279/PIP.070010 Cite as: M Perfetti, Papers in Physics 7, 070010 (2015)